Minimization of Insect Pest Attacks with the Concept of Urban Farming Agriculture (Sainteknol : Jurnal Sains dan Teknologi, 2022)
Urban Farming is an agricultural system without the use of soil media that utilizes narrow land in urban areas and is free from the use of synthetic pesticides. This study aims to identify the types and abundance of insects that attack cultivated plants in Urban Farming. Data collection was carried out by observation using the yellow pan, netting, and hand picking methods. Insect identification is carried out on the basis of morphological features of insects. The data were analyzed with the insect abundance index (Di). The results showed that the highest insect abundance found at the Urban Farming Surabaya agricultural location was  Aphis gossypii with an abundance index value of 26.37% and the lowest insect abundance was Hishimonus spatulatus, Meniscus midge, Murgantia histrionica, Mylabris phalerata with an abundance index value of 0.34%. Where found 34 species of insects with 27 families namely the family Acrididae, Agromyzidae, Aleyrodidae, Aphididae, Apidae, Calliphoridae, Chrysomelidae, Cicadelloidae, Coccinellidae, Crambidae, Dixidae, Dolichopodidae, Gryllidae, Hesperiidae, Meloidae, Muscidae, Noctuidae, Pentatomidae, Pieridae, Pseudococcidae, Psilidae, Sapygidae, Staphylinidae, Stratiomyidae, Syrphidae, Tetranychidae and Thripidae.